Pengaruh Strategi Diferensiasi Produk Terhadap Loyalitas Konsumen pada Kedai Kopi Kinikawa di Pangkal Pinang - Hashya Olivia Balqis; Rahma Gusti Pratama; Khusna Khusna; Indah Noviyanti (Pusat Riset dan Inovasi Nasional, 2025)
In today's highly competitive culinary industry, one of the most important strategies to attract and retain customers is product differentiation. Differences can provide value and set a business apart from its competitors. Examples of differentiation include innovative menu items, premium raw materials, distinctive flavors, and brand image. The goal of this study is to analyze the relationship between product differentiation and customer loyalty at Kinikawa Coffee Shop in Pangkal Pinang. As part of a quantitative research plan using survey techniques, questionnaires were distributed to one hundred active customers. The validity and reliability of the research instrument were examined, and simple linear regression analysis of the data was performed using SPSS software. The findings of the study indicate that customer loyalty is positively related. Customer loyalty to Kinikawa increases along with their opinions regarding the company's efforts to stand out from the competition.. This research highlights the importance of using differentiation tactics when building lasting relationships with clients, especially in the local coffee shop industry facing tight and fluctuating competition.